2012
DOI: 10.1097/hcr.0b013e31825828da
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Reduces Sympathetic Nervous Activity and Improves Inspiratory Muscle Weakness and Quality of Life in Patients With Chronic Heart Failure

Abstract: Home-based IMT represents an important strategy to improve cardiac and peripheral autonomic controls, functional capacity, and quality of life in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(133 citation statements)
references
References 30 publications
4
124
1
4
Order By: Relevance
“…In turn, respiratory muscle exercises are a nonpharmacological strategy widely used to improve functional capacity in several conditions associated with the impaired respiratory muscle strength, such as chronic obstructive pulmonary disease (Petrovic et al, 2012), chronic heart failure (Mello et al, 2012) and hypertension (Ferreira et al, 2013), along with another aging-associated conditions (Aznar-Lain et al, 2007). Furthermore, studies have demonstrated beneficial effects of inspiratory muscle exercise (IME) on cardiac autonomic function, indicated by reduced sympathetic modulation and increased vagal modulation in young smokers (Rodrigues et al, 2013), as well as hypertensive (Ferreira et al, 2013) and heart failure patients (Mello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, respiratory muscle exercises are a nonpharmacological strategy widely used to improve functional capacity in several conditions associated with the impaired respiratory muscle strength, such as chronic obstructive pulmonary disease (Petrovic et al, 2012), chronic heart failure (Mello et al, 2012) and hypertension (Ferreira et al, 2013), along with another aging-associated conditions (Aznar-Lain et al, 2007). Furthermore, studies have demonstrated beneficial effects of inspiratory muscle exercise (IME) on cardiac autonomic function, indicated by reduced sympathetic modulation and increased vagal modulation in young smokers (Rodrigues et al, 2013), as well as hypertensive (Ferreira et al, 2013) and heart failure patients (Mello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated beneficial effects of inspiratory muscle exercise (IME) on cardiac autonomic function, indicated by reduced sympathetic modulation and increased vagal modulation in young smokers (Rodrigues et al, 2013), as well as hypertensive (Ferreira et al, 2013) and heart failure patients (Mello et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, no adverse effects have been reported in CHF patients, indicating that IMT is a safe tool to improve inspiratory muscle strength [75]. Furthermore, IMT and ExT reduce sympathetic drive, which might lead to improvements in cardiac function and respiratory drive [76]. Most importantly, CHF and PAH patients report a better quality of life and decreased sensation of dyspnoea on exertion after IMT [69,70,74].…”
Section: Inspiratory Muscle Trainingmentioning
confidence: 93%
“…HR variability was analyzed in the frequency domains during the protocol, as previously described (Mello et al, 2012). The spectral bands for humans (very low frequency—VLF, 0.0–0.04 Hz; low frequency—LF, 0.04–0.15 Hz; and high frequency—HF, 0.15–0.4 Hz) were defined according to the literature (Pagani et al, 1986).…”
Section: Methodsmentioning
confidence: 99%